Design of a Sobel Edge Detection Algorithm on FPGA - et. al., Sudharshan K.M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we see the advantage to realize a real time parallel processing of image data comes with the use of Field Programmable Gate Array (FPGA). This paper highlights on the use of image edge detection, mainly turning the focus on a gradient filter, the Sobel filter. Here we design a Sobel edge detection algorithm to define the edge for a given gray scale image choosing the Zynq Development target board on Vivado software.